Expression of HMGB1 and NF-κB p65 and its significance in non-small cell lung cancer - Zhang, Xiaohong; Wang, Hongmin; Wang, Jing (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To study high mobility group protein B1 (HMGB1) and nuclear transcription factor p65 (NF-κB p65) expression in non-small cell lung cancer and its significance. Material and methods : 106 hospitalized patients with non-small cell lung cancer after thoracic surgery were enrolled; HMGB1 and p65 protein expression was detected by the immunohistochemical method. Semiquantitative expression of HMGB1 and NF-κB p65 was analyzed using Image Pro Plus (IPP) software and statistical analysis. Results: The rate of HMGB1 positive expression in the non-small cell lung cancer protein B1 family was significantly higher than normal tissues (P < 0.05); p65 protein expression in the non-small cell lung carcinoma group was significantly higher than that of normal tissues (P < 0.05). HMGB1 and NF-κB p65 protein expression was significantly higher compared with the non-metastatic group (P < 0.01). HMGB1 and NF-κB p65 protein expression showed a positive correlation (P < 0.05). Conclusions : HMGB1 and NF-κB p65 expression may be related to non-small cell lung cancer metastasis.